Stress resistance and adaptive capacities of cardiovascular system of graduating teenagers with different level of studying load - Olena Khomenko; Oleh Nekhanevych; Sofiia Simonova; Yevgeniia Kovalenko; Valentin Kosse; Elvira Topka (Kazimierz Wielki University, 2021)
The analysis of stress resistance and adaptive reactions of cardiovascular system was conducted according to the level of heart rate variability of graduating teenagers regardless of their studying load. The survey was held in Dnipro (Ukraine) based on a method of anonymous questioning using a personally developed and standardized questionnaire. 84 teenagers that are students of the 11th form of comprehensive schools and lyceums were asked. 22 children of relevant age from different countries made up a comparison group, among them an online survey was conducted by means of similar English-language questionnaire in Google-form. The assessment of heart rate variability of 46 graduates was given, using a cloud technology of automated interpretation of ECG (PRECISE). Statistical processing was conducted using the application program Statistica 6.0 for Windows. Decreasing of stress resistance and significant violations of adaptive cardiovascular reactions in teenagers of graduating classes in Dnipro was set, especially in lyceum students as a result of insufficient rest of students. During the educational period significant violation of adaptive capabilities takes place in 65.6 % of lyceum students: exhausting of functional organism's reserves with decline in RMSSD to (17.2±1.9) meters per second, Total power to (607.25±11.9) meters per second has been observed in half of the students. At the same time, 85.3 % of the comprehensive school students have sufficient adaptive and worse resource capacities of an organism. For the first time it was highlighted that the autonomous nervous system among the examined teenagers operates in the imbalance regime of its sympathetic and parasympathetic link with a prevalence of sympathicotonia among the 50 % of lyceum students during a recessional period, 56.3 % during an educational period, while vagotonia and eutonia prevail among the comprehensive school students, not depending on the school year period. It was found out that physical activity promoted increased body resistance to stress factors. The efficient determination of heart rhythm variability (PRECISE diagnostics) was proven to control the functional state and adaptive capabilities of graduates' cardiovascular system.